(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Alzheimer’s disease is a brain related issue which effects the mental stability of a person. It degrades the thinking capability and targets the memory of a person.The person who is effected with the Alzheimer’s finds difficult to even remember simple daily things[8].Even the very recent or latest event is also difficult for them to remember or keep track of.TheAlzheimer’s disease is challenging one because there is no treatment for the disease. This disease is currently ranked as the seventh leading cause of death in the United States among older adults.There is no permanent cure or treatment for this. Thus, if the disease is predicted earlier, the progression or the symptoms of the disease can be slow down. In this paper we intend to create a model that detects Alzheimer disease using GAN and CNN.GAN can be adopted to fulfil the role of data augmentation. GANs are generative models: they create new data instances that resemble your training data. Classification process can be fulfilled by using the CNN model to the data for improving the efficiency and to ensure higher accuracy.